Investigation on dynamic characteristics of herringbone planetary gear transmission system with staggered tooth phase - Shaoshuai Hou; Haichao Ye; Derong Zhu; Shijie Zhang; Jingjing Li; Ming Xia; Sicheng He (PLoS ONE, 2026)
Vibration and noise are critical indicators that directly affect the transmission characteristics of planetary gearboxes. Consequently, the suppression of vibration and noise has emerged as a major research focus in this field. This paper investigates the meshing mechanism of herringbone planetary gear systems with staggered tooth phase (STP), and derives the analytical formulation for calculating the time-varying mesh stiffness (TVMS) of such gear configurations. In addition, it examines the correlation between the staggered tooth phase angle (STPA) and the system vibration response, as well as the dynamic effects induced by variations in rotational speed and different types of tooth profile errors. The results demonstrate that the implementation of STP could substantially enhance the vibration characteristics of herringbone planetary gear systems. Furthermore, among various tooth profile errors, the single tooth tangential error (STTE) is identified as the dominant factor governing vibration.